Calculation of climatic reference values and its use for automatic outlier detection in meteorological datasets - B. Téllez; T. Cernocky; E. Terradellas (Advances in Science and Research, 2008)
The climatic reference values for monthly and annual average air temperature and total precipitation in Catalonia – northeast of Spain – are calculated using a combination of statistical methods and geostatistical techniques of interpolation. In order to estimate the uncertainty of the method, the initial dataset is split into two parts that are, respectively, used for estimation and validation. The resulting maps are then used in the automatic outlier detection in meteorological datasets.